Association between Chronic Urticaria and Helicobacter Pylori Infection in Patients Visiting a Tertiary Hospital - Zartaj Liaqat, Sabah Ibad, Seemab Khan, Muhammad Farooq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to demonstrate the association between chronic urticaria and H.pylori infection for effective management of chronic urticaria. Methodology: A case-control study was conducted in the Dermatology Department of Bakhtawar Amin Trust Hospital Multan from 30th Jan 2020 to 30th Jan 2021. The patients who recently visited the inpatient or outpatient ward of the hospital were a part of the study whereas the patients who were administered proton pump inhibitors or any antibiotics in the last 1 month were excluded from the study. The patients diagnosed with chronic urticaria were asked to collect one gram of stool and submit the sample. The sample was stored at -20 Celsius and tested for H.pylori infection. The strength of association between chronic urticaria and H.pylori infection was measured by conditional logistic regression. Two-tailed p values were noted and p<0.05 was regarded as statistically significant Results: The study included 80 patients (40 controls and 40 cases). The median age was 32 years in controls while 35 years in cases. Both groups had a majority (n=56, 70%) of females. More than one half (n=23, 57%) of cases and controls (n=27, 67%) lived in urban region. There was a significant difference between the percentage of those who tested H.Pylori positive and had CU and those who were H.Pylori positive but did not have CU. In subjects infected with H.Pylori risk of CU is six times higher than those not infected Conclusion: Relation between H.Pylori and Chronic urticaria is significant, which indicates H.Pylori tests for diagnosis of CU. Keywords: Chronic Urticaria, H.Pylori, Stool antigen test